Prospects and challenges for fungal metatranscriptomics of complex communities. (April 2015) - Kuske, Cheryl R.; Hesse, Cedar N.; Challacombe, Jean F.; Cullen, Daniel; Herr, Joshua R.; Mueller, Rebecca C.; Tsang, Adrian; Vilgalys, Rytas
Abstract: The ability to extract and purify messenger RNA directly from plants, decomposing organic matter and soil, followed by high-throughput sequencing of the pool of expressed genes, has spawned the emerging research area of metatranscriptomics. Each metatranscriptome provides a snapshot of the composition and relative abundance of actively transcribed genes, and thus provides an assessment of the interactions between soil microorganisms and plants, and collective microbial metabolic processes in many environments. We highlight current approaches for analysis of fungal transcriptome and metatranscriptome datasets across a gradient of community complexity, and note benefits and pitfalls associated with those approaches. We discuss knowledge gaps that limit our current ability to interpret metatranscriptome datasets and suggest future research directions that will require concerted efforts within the scientific community.